An Exploration of Process Improvement in Project Management at Experian plc - Matthews, Louisa (2008)
The project reviews the "as is" process utilised at Experian in product development & delivery. Issues as to process improvement, governance and knowledge management are considered within the software project management context and both overarching and detailed recommendations are made to inform ongoing process evolution at Experian.